Review Paper on the Demand Response Programs and the Intention to Accept Them as a Solution for Increasing Demand of Electricity - Samar Abdulrazzaq Mohammed AL-GHALEBI; Ahmed Saleh Ahmed Saif AL-SHAMERI; Zainon Mat SHARIF; Saba’a Saleh Ahmed SAIF; Saleh Ibrahim Mohammed AL AAMRI (Communications of International Proceedings, 2020)
Increasing demand of electricity is a problematic issue nowadays. Two main strategies are used in the power system operation to face this issue that are reducing the electricity demand or increasing the electricity generation. However, literature review have proven Demand Side Management Programs to be the best solution for the increasing demand of electricity with the problem of level of acceptance of such programs among the nations. Thus, this review paper is aimed at reviewing the available literature on the acceptance of Demand Response Programs which special focus on the the Gulf countries. The paper has also reviewed the important factors that have an impact on the intention of people to accept such programs.